Conceptual approach to introduction of information technology into the field of simulation - Andreev, A. N.; Blinov, A. V.; Yurkov, N. K.; Yakimov, A. N. (Measurement techniques, 1999)
We consider results of research by the faculty for design and production of radio equipment at Penza State University; the research was concerned with development of methods, models, algorithms, and software packages for investigating complex mechanical systems, technologies, and simulation of physical processes.[PUBLICATION ABSTRACT]